2016
DOI: 10.5005/jp-journals-10024-1828
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Methodology to detect Leaching of Nickel and Chromium Ions in the Initial Phase of Orthodontic Treatment: An in vivo Study

Abstract: Nickel and chromium levels were well within the permissible levels. However, some hypersensitive individuals may be allergic to this minimal permissible level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Table 2 shows the characteristics of 14 studies included in this meta-analysis. Four studies had been conducted in India [2,10,22,23], three in Iran [24,25,26], one in Norway [5], one in Turkey [13], one in Brazil [11], one in Greece [4], one in Morocco [6], one in Saudi Arabia [15], and one in Germany [1]. Two studies [1,22] reported the median (quartile) of the salivary level of ions, two studies [4,5] reported the median (range), and one study [6] reported the mean (range) values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the characteristics of 14 studies included in this meta-analysis. Four studies had been conducted in India [2,10,22,23], three in Iran [24,25,26], one in Norway [5], one in Turkey [13], one in Brazil [11], one in Greece [4], one in Morocco [6], one in Saudi Arabia [15], and one in Germany [1]. Two studies [1,22] reported the median (quartile) of the salivary level of ions, two studies [4,5] reported the median (range), and one study [6] reported the mean (range) values.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [1,22] reported the median (quartile) of the salivary level of ions, two studies [4,5] reported the median (range), and one study [6] reported the mean (range) values. Three studies [2,6,23] had only evaluated one assessment period of orthodontic treatment. Three studies did not report the mean age [1,2,11].…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al [ 37 ] evaluated the release of nickel and chromium ions in human saliva during fixed orthodontic therapy, pointed out on more intense release during the initial phase, by measuring the level of metal ions in saliva (by ICP-OES). The levels of nickel and chromium were statistically significantly higher, while nickel showed a gradual increase in the first 10 days with a further decline.…”
Section: Discussionmentioning
confidence: 99%